\[\boxed{\text{669\ (669).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[3x^{2} - x + 7 = 10\]
\[3x^{2} - x - 3 = 0\]
\[3x^{2} - x = 3\]
\[6x^{2} - 2x + 7 =\]
\[= 2 \cdot \left( 3x^{2} - x \right) + 7 =\]
\[= 2 \cdot 3 + 7 = 13\]
\[Ответ:13.\]
\[\boxed{\text{669.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ a^{8} - b^{8} =\]
\[= \left( a^{4} - b^{4} \right)\left( a^{4} + b^{4} \right) =\]
\[2)\ a^{16} - 256 =\]
\[= \left( a^{8} - 16 \right)\left( a^{8} + 16 \right) =\]
\[= \left( a^{4} - 4 \right)\left( a^{4} + 4 \right)\left( a^{8} + 16 \right) =\]